The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1093/hmg/10.18.1907
|View full text |Cite
|
Sign up to set email alerts
|

Genetic model of multi-step breast carcinogenesis involving the epithelium and stroma: clues to tumour-microenvironment interactions

Abstract: Although numerous studies have reported that high frequencies of loss of heterozygosity (LOH) at various chromosomal arms have been identified in breast cancer, differential LOH in the neoplastic epithelial and surrounding stromal compartments has not been well examined. Using laser capture microdissection, which enables separation of neoplastic epithelium from surrounding stroma, we microdissected each compartment of 41 sporadic invasive adenocarcinomas of the breast. Frequent LOH was identified in both neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
2
7

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 27 publications
2
134
2
7
Order By: Relevance
“…However, the recent finding of frequent genetic changes in mammary stromal tissue in breast cancer patients (Moinfar et al, 2000), and the demonstration that inflammation-associated stroma promotes conversion of colonic adenoma cells to adenocarcinoma cells in nude mice (Okada et al, 2000) suggest a more complex scenario. Our present study showed that MSI in stromal and epithelial elements can occur independently in sporadic colorectal cancers, in line with the previous findings for breast carcinomas (Kurose et al, 2001). Further, while MSI in the epithelium tended to correlate with differentiation and the Dukes' stage, the inverse was the case for MSI in stroma.…”
Section: Discussionsupporting
confidence: 92%
“…However, the recent finding of frequent genetic changes in mammary stromal tissue in breast cancer patients (Moinfar et al, 2000), and the demonstration that inflammation-associated stroma promotes conversion of colonic adenoma cells to adenocarcinoma cells in nude mice (Okada et al, 2000) suggest a more complex scenario. Our present study showed that MSI in stromal and epithelial elements can occur independently in sporadic colorectal cancers, in line with the previous findings for breast carcinomas (Kurose et al, 2001). Further, while MSI in the epithelium tended to correlate with differentiation and the Dukes' stage, the inverse was the case for MSI in stroma.…”
Section: Discussionsupporting
confidence: 92%
“…1 Since publication of our previous observation, several other groups have confirmed the occurrence of genetic abnormalities in the normal-appearing stromal cells close to the breast carcinomas. [2][3][4][5] In the current study, we provide, for the first time, evidence of common genetic alterations in the tumor-free and morphologically normal-appearing mammary skin of the patients with breast cancer. These data have implications for understanding of tumorigenesis in general and of breast cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] These data strongly suggest that genetic abnormalities in microenvironmental tissues with subsequent alterations of reciprocal interactions between epithelial and stromal cells play a key role in the tumorigenesis of breast cancer. In our previous study, we showed that loss of heterozygosity (LOH) frequently occurs in the tumor-free and normal-appearing epithelial and mesenchymal tissue components close to and away (at least 15-mm distance) from the breast cancer tissues.…”
mentioning
confidence: 99%
“…However, it has become clear from preliminary trials that a number of anti-angiogenic drugs or strategies can lose their activity over time (26,27). Several potential mechanisms have been evocated, such as the great redundancy of tumor-secreted angiogenic growth factors and the anti-apoptotic properties of TEC dependent either on direct tumor-endothelial cell interaction or on epigenetic changes occurring after persistent cell activation (28). Recently, it has been reported that tumor endothelium has, at the molecular level, distinct characteristics from normal endothelial cells (15) and may be resistant to apoptosis (14,29).…”
Section: Discussionmentioning
confidence: 99%